2003
DOI: 10.1074/jbc.m205484200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the (R)-Specific Enoyl-CoA Hydratase from Aeromonas caviae Involved in Polyhydroxyalkanoate Biosynthesis

Abstract: The (R)-specific enoyl coenzyme A hydratase ((R)-hydratase) from Aeromonas caviae catalyzes the addition of a water molecule to trans-2-enoyl coenzyme A (CoA), with a chain-length of 4-6 carbons, to produce the corresponding (R)-3-hydroxyacyl-CoA. It forms a dimer of identical subunits with a molecular weight of about 14,000 and is involved in polyhydroxyalkanoate (PHA) biosynthesis. The crystal structure of the enzyme has been determined at 1.5-A resolution. The structure of the monomer consists of a five-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
95
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 46 publications
1
95
0
Order By: Relevance
“…1 c and d). Other reported oligomeric structures of microbial thioesterases include dimers (20,21) and different tetrameric arrangements (14,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…1 c and d). Other reported oligomeric structures of microbial thioesterases include dimers (20,21) and different tetrameric arrangements (14,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…It is a putative (R)-specific enoyl hydratase/3-hydroxyacyl dehydratase belonging to the hydratase 2 protein family and it holds a well-conserved hydratase 2 motif, including the catalytic residues "D-x(4)-H" (5,29). It is predicted to have a "double hot dog fold" structure (5,29), where each of the two structural domains corresponds to a hot dog fold (mainly a long ␣-helix wrapped into a fivestranded antiparallel ␤-sheet [13]). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the crystal structure of Aeromonas caviae (R)-specific enoyl-CoA hydratase was resolved, and the catalytic residues were suggested to be Asp-31 and His-36 (11). Also, these amino acids were found to be highly conserved in various (R)-hydratases (11). Multiple alignment of MaoC and PhaJ1 clearly showed that these essential amino acid residues also exist in MaoC at conserved region (Fig.…”
mentioning
confidence: 97%
“…These results might have resulted from the presence of various FadB homologous enzymes mentioned above. Recently, the crystal structure of Aeromonas caviae (R)-specific enoyl-CoA hydratase was resolved, and the catalytic residues were suggested to be Asp-31 and His-36 (11). Also, these amino acids were found to be highly conserved in various (R)-hydratases (11).…”
mentioning
confidence: 99%